Montelukast Drug May Improve COVID-19 Prognosis: A Review of Evidence - Barré, Jean; Sabatier, Jean-Marc; Annweiler, Cédric (Frontiers in Pharmacology, 2020)
With the lack of effective therapy, chemoprevention and vaccination, focusing on the immediate repurposing of existing drugs gives hope of curbing the pandemic. Interestingly, montelukast, a drug usually used in asthma, may be proposed as a potential adjuvant therapy in COVID-19. The aim of the present article was to review the properties of montelukast that could be beneficial in COVID-19. Ten experimentally supported properties were retrieved, either related to SARS-CoV-2 (antiviral properties, prevention of endotheliitis and of neurological disorders linked to SARS-CoV-2), and/or related to the host (improvement of atherogenic vascular inflammation, limitation of the ischemia/reperfusion phenomenon, improvement of respiratory symptoms), and/or related to serious COVID-19 outcomes (limitation of the cytokine storm, mitigation of acute respiratory distress syndrome), and/or related to tissue sequelae (antioxidant properties, anti-fibrosis effects). Based on gathered theoretical evidence, we argue that montelukast should be further tested to prevent and treat COVID-19 outcomes.